Reconstructing Dalit Masculinities: A Study of Select Dalit Autobiographies. (July 2022) - Mukherjee, Riya; Jha, Smita
The study of masculinities in India has largely been confined to the analysis and understanding of the upper caste hegemonic masculinity and complicit masculinity, with respect to emphasised femininity. The issue of Dalit masculinities has been subsumed in the larger discourse of South Asian masculinity. The present study intends to address this gap by delving into the nuances of Dalit masculinities through a detailed analysis of Aravind Mālagatti's Government Brahmana and Baby Kamble's The Prisons We Broke . The study would employ the categories of masculinities enunciated by Connell, while using a post-structuralist lens to question their absoluteness. In the process, the study would challenge the monolith of masculinity in general and Dalit masculinity in particular, which instead of being rigid and irrevocable has a plural and fluid identity.